Обґрунтування основних показників і залежностей інвестиційної привабливості машинобудівних підприємств - Стригуль, Лариса Станіславівна (Донецький державний університет управління, 2013)
У статті досліджено сучасні проблеми актуалізації напрямків та визначення існуючих можливостей активізації інвестиційних процесів в умовах сучасного господарювання, пов’язаного з великою кількість впливів зовнішнього та внутрішнього характеру на рівень інвестиційної привабливості машинобудівних підприємств. Проаналізовано існуючі методичні підходи оцінки інвестиційної привабливості підприємств.

In article modern problems of actualization of directions and determination of existing possibilities of activation of investment processes in the conditions of the modern managing connected with big quantity of the influences of external and internal character on level of investment appeal of the machine-building enterprises are researched. It is analyzed existing methodical approaches of an estimation of investment appeal of the enterprises. The system of indicators and dependences of investment appeal of the enterprises of machine-building area is specified and proved. The analysis of dependences of investment activity of the machine-building enterprise from its results is carried out is production-economic activities, which is based on consolidation of methods: a method of "a stony talus" for the justification of optimum quantity of factors of influence on investment activity; The factorial analysis for determination of quantitative influence on investment activity of the revealed factors.
The justification of the main indicators of the dependency and invest attractiveness of the engineering enterprises
Keywords: інвестиції; оцінка інтегральна; стан фінансовий; показники; investments; investment appeal; integrated estimation